2004
DOI: 10.1037/1093-4510.7.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Between the Cup of Principle and the Lip of Practice: Ethnic Minorities and American Psychology, 1966-1980.

Abstract: By 1980, the previously held dichotomy of Black and White racial identity in America had yielded to a mosaic of red, yellow, brown, black, and white. During the 1960s and 1970s, identity, and thus psychological knowledge, were articulated and differentiated in terms of gender, sexual orientation, and class in unprecedented ways. In this article, the author contextualizes efforts to make mainstream American psychology more receptive to ethnic minorities between 1966 and 1980. Advocacy and activism by ethnic min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…A parallel interest in racial ethnic psychology (Leong, 2009;Pickren, 2004) rejected the Anglo-American framing of ''race psychology'' (see Richards, 1997, for a history of race psychology), but concern with other social identities, such as social class (Lott & Bullock, 2007), came much later. In any event, these identity-based areas of research developed essentially independently of one another.…”
Section: Behavioral Sex Differencesmentioning
confidence: 99%
“…A parallel interest in racial ethnic psychology (Leong, 2009;Pickren, 2004) rejected the Anglo-American framing of ''race psychology'' (see Richards, 1997, for a history of race psychology), but concern with other social identities, such as social class (Lott & Bullock, 2007), came much later. In any event, these identity-based areas of research developed essentially independently of one another.…”
Section: Behavioral Sex Differencesmentioning
confidence: 99%
“…For example, more than one-third of individuals identified as prominent who entered the field since 1990 are ethnic minorities. These trends are particularly encouraging as other fields of psychology struggle to recruit and retain ethnic minority members (Commission on Ethnic Minority Recruitment, Retention, and Training in Psychology [CEMRRAT], 1997;Pickeren, 2004). In an article published in the American Psychologist, Ken Maton and his colleagues reported that ethnic minorities are less likely than non-minorities to enter or finish a doctoral program in psychology (Maton, Kohout, Wicherski, Leary, & Vinokurov, 2006).…”
Section: Inclusion Of Marginalized Groupsmentioning
confidence: 99%
“…These EMPAs formed in the late 1960s and early 1970s and have a 40-year-plus history of existence. ABPsi was founded in 1968; the Association of Psychologists por la Raza, a precursor to NLPA, was founded in 1970; AAPA was founded in 1972; SIP was founded 1973; and Division 45 was founded in 1986 (Pickren, 2004).…”
mentioning
confidence: 99%